Women and family life: a comparative analysis of Arabic and Malay folk tales - Ahmad H.Osman, Rahmah; Jaffer, Usman; Ariffin, Nur Aini; Toyyib Abiodun, Mustapha; Suleiman, Amany; Alzeheimi, Saleh (Northeastern University, 2022)
Literary writers have divided Arabic literature mainly into two complementary areas –poetry and prose. This article attempts to offer a comparative analysis research focusing on the image of women in family life as mothers, wives, and sisters in both Arabic and Malay folk tales. It is based on selected stories from two famous books: Hikayat Sha'biyyah by Ahmad Ziyād Mahbak and Himpunan 366 Cerita Rakyat Malaysia by Othman Puteh and Aripin Said. This study adopts literary analysis and comparative methods. Therefore, through these methods the image of women in family life as a mother, wife, and sister in selected texts are introduced. The comparative method has also been used to do a comparative analysis between the image of women in Arabic and Malay folk tales. This study reveals that the image of women in both folk tales shares several common features, suggesting the universality of folk tales. There are also minor differences between the two genres of folk tales because of factors such as environmental and cultural differences and the taleteller’s inclinations and preferences.